2009
DOI: 10.1371/journal.pone.0004459
|View full text |Cite
|
Sign up to set email alerts
|

The SmpB-tmRNA Tagging System Plays Important Roles in Streptomyces coelicolor Growth and Development

Abstract: The ssrA gene encodes tmRNA that, together with a specialized tmRNA-binding protein, SmpB, forms part of a ribonucleoprotein complex, provides a template for the resumption of translation elongation, subsequent termination and recycling of stalled ribosomes. In addition, the mRNA-like domain of tmRNA encodes a peptide that tags polypeptides derived from stalled ribosomes for degradation. Streptomyces are unique bacteria that undergo a developmental cycle culminating at sporulation that is at least partly contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 58 publications
2
14
0
Order By: Relevance
“…In this report, we show that ClpP protease is required for SigT protein degradation to remove its inhibitory effects on cell differentiation. This is consistent with the phenotypes of the ⌬clpP and ⌬ssrA mutants that display delayed morphological development and secondary metabolism (41,43). Furthermore, SigT negatively regulates the clpP1/P2 gene expression by binding to its promoter.…”
Section: Discussionsupporting
confidence: 86%
“…In this report, we show that ClpP protease is required for SigT protein degradation to remove its inhibitory effects on cell differentiation. This is consistent with the phenotypes of the ⌬clpP and ⌬ssrA mutants that display delayed morphological development and secondary metabolism (41,43). Furthermore, SigT negatively regulates the clpP1/P2 gene expression by binding to its promoter.…”
Section: Discussionsupporting
confidence: 86%
“…Several groups have developed tmRNA variants that encode various epitope tags that are resistant to proteolysis (Fig. 2 and Section III) (Barends et al, 2010; Fujihara et al, 2002; Gottesman et al, 1998; Roche and Sauer, 2001; Thibonnier et al, 2008; Yang and Glover, 2009). These tmRNA variants allow tagging activity to be assessed by immunoblot and have facilitated the identification of several ssrA-tagged proteins in a variety of bacteria (Barends et al, 2010; Collier et al, 2002; Fujihara et al, 2002; Roche and Sauer, 2001).…”
Section: Tmrna•smpb and The Mechanism Of Trans-translationmentioning
confidence: 99%
“…This ssrA(DD) peptide tag is also resistant to degradation in the cytoplasm (Keiler et al, 1996), and several studies have shown that the hydrophobic C-terminus of ssrA is critical for degradation by cytoplasmic proteases (Flynn et al, 2001; Gottesman et al, 1998; Herman et al, 1998). This recognition mode is highly conserved throughout eubacteria and tmRNA variants encoding charged C-terminal residues have been used to stabilize tagged proteins in a variety of species (Fujihara et al, 2002; Hong et al, 2007; Keiler and Shapiro, 2003b; Thibonnier et al, 2008; Wiegert and Schumann, 2001; Yang and Glover, 2009). …”
Section: Degradation Of Ssra-tagged Proteins and Truncated Mrnamentioning
confidence: 99%
“…2 to 4% of all protein chains are tagged by the tmRNA system (66), indicating that the tmRNASmpB system plays an important and general role in bacterial pathogenesis (67). In bacteria, the tmRNA quality control system is the primary mediator of ribosome rescue and thus is critical for several aspects of bacterial fitness, including growth and development, stress responses, and pathogenesis (29,68,69). Further investigations are required to fully elucidate the mechanism by which the tmRNA-SmpB system influences the pathogenesis of APEC.…”
Section: Discussionmentioning
confidence: 99%